Phytosterol from the leaves of Vernonia conferta Benth (Asteraceae) - Umoh, Ifiok James; Eseyin, Olorunfemi A.; Ahmadu, Augustine A. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
From the dichloromethane soluble part of ethanol extract of the leaves of Vernonia conferta, a phytosterol, Stigmast-5-ene-3?-ol (?-sitosterol) was isolated for the first time from this plant. The structure was elucidated using NMR and MS and was compared with literature.